(untitled) (Research, Society and Development, 2024)
This study aimed to evaluate the effect of different concentrations of the bio-stimulant Stimulate® on overcoming dormancy, germination, and development of flamboyant seedlings (Delonix regia). Concentrations of Stimulate® used were 2.5; 5.0; 7.5; and 10.0 ml L-1, with seeds soaked for one hour. The seeds tested included those with intact teguments and those scarified with water sandpaper No. 120 on the side opposite the embryo, following a 5x2 factorial scheme. The treatments were arranged in a completely randomized design, with seeds sown in tubes containing commercial substrate. The results showed a significant interaction (p<0.05) between the bio-stimulant and mechanical scarification factors for all analyzed variables. The combination of Stimulate® with mechanical scarification favored the germination of flamboyant seeds. However, mechanical scarification alone resulted in greater leaf formation and superior growth in both height and diameter of the seedlings. Thus, while the combination of bio-stimulant and scarification promoted germination, scarification alone was sufficient for better seedling development, making the use of the bio-stimulant unnecessary.